In vitro anti-Toxoplasma effects and apoptotic induction of queen bee acid (10-hydroxy-2-decenoic acid) alone and in combination with atovaquone - Asgari, P.; Pourhossein, Siavash (Razi Vaccine and Serum Research Institute, 2024)
Toxoplasmosis, which is caused by the Toxoplasma gondii parasite, is a parasitic, infectious disease. 10-hydroxy-2-decenoic acid (10-H2DA, queen bee acid (QBA), is one of the most prevalent fatty acids (>40%) present in royal jelly. Studies have pointed to antitumor, anti-inflammatory, antiangiogenic, and antimicrobial effects of 10-H2DA, improving the immune system. This experimental survey aimed to assess the in vitro efficacy of QBA against tachyzoites and intracellular parasites of the T. gondii RH strain. Anti-Toxoplasma effects of QBA against tachyzoites were examined by MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay for 30, 60, 120, and 180 min. In addition, the effect of QBA on infection rate and intracellular parasites was studied. Real-time polymerase chain reaction (Real-Time PCR) was also applied to assess the expression level of the Caspase-3 gene. The best efficiency of QBA was obtained at 100 and 50 µg/mL, whereas all tachyzoites were diminished, followed by 120- and 180-min treatment, respectively. It was also found that the best repressing efficacy of QBA in the infection rate and the load of parasites into the Vero cells was indicated at 100 µg/mL (P<0.001). Nonetheless, the combination of QBA (12.5 µg/mL) along with atovaquone 30 µg/mL displayed the most marked effect on the infection rate and a load of parasites into the Vero cells in the infected Vero cells. The expression level of the Caspase-3 gene was dose-dependently increased after the exposure of tachyzoites to QBA, mainly at ½ IC50 and IC50 compared to normal saline. The obtained findings exhibited the high in vitro potency of QBA, especially in combination with atovaquone against T. gondii RH strain tachyzoites. Although apoptosis induction can be suggested as one of the principle mechanisms, more studies are required to elucidate its accurate mechanisms, as well as its efficacy and safety in animal models and clinical settings. © 2024 Razi Vaccine and Serum Research Institute. All rights reserved.
Keywords: Apoptosis; In vitro; Tachyzoites; Toxoplasmosis